ASPEK HUKUM TERHADAP PEJABAT PEMBUAT AKTA TANAH SEMENTARA YANG DILAKUKAN OLEH CAMAT DI DALAM WILAYAH KERJANYA - , HELGA EVELINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the implementation of the Land Deed Official Position While that is done by sub district head in the working area and to determine the duties and authority of the Land Deed Official Meanwhile conducted by the sub district heads in the working area. The nature of research used in this research is research normative law, where research law normative is that research done by means of researching material pustaka or data secondary.All the data been obtained from research, next analyzed in a qualitative juridical.Research it starts with determine beforehand existing in exercise of authority subdistrict as officials pembua certificate meanwhile, the ground then make draft of trouble and title.Next gathering materials laws relating to the main issues and memilahnya according to the so ease in doing analysis Based on the result of the study, could be noticed that in running his term of office as an official a maker of deed of the ground while sub-district it must necessarily hold it firm staple a tenure by which implemented in accordance with the regulations. Any sub district, should be seized control of the and is expected to increase of knowledge, and education either through education remains as well as trainings in the field of defence to at least reduce problem and reduce the problems that will arise. Key word : PPAT Sementara, Camat, the sub working area